Ensayar sobre los ‘tiempos idos’, marcar nuestra presencia: Carta a un padre y Sara de Edgardo Cozarinsky - Maya González Roux (Cuadernos LIRICO)
In the film Carta a un padre (2013) and the book Sara (2013), Edgardo Cozarinsky explores not so much the lives of his parents but the “gone times”, a dead past made of relics, remains, and silences. Through the continuous digressions, so characteristic of his cinematic and literary narratives, this article aims to address the work with intimacy, always intertwined with an era, and to observe the oscillation between fiction and document, between chronicle, essay, and life writing.